Risk-taking behavior in the wake of natural disasters - Lisa Ann Cameron; Manisha Shah (Institute for the Study of Labor (IZA), 2012)
We study whether natural disasters affect risk-taking behavior exploiting geographic variation in exposure to natural disasters. We conduct standard risk games (using real money) with randomly selected individuals in Indonesia and find that individuals who recently suffered a flood or earthquake exhibit more risk aversion than individuals living in otherwise like villages. The impact persists for several years, particularly if the disaster was severe. Some, but not all, of this effect is due to income losses. While we cannot rule out fundamental changes in risk preferences, data on subjective beliefs of the probability of a disaster occurring and the expected severity of such a disaster suggest that changes in perceptions of background risk are driving the more risk-averse behavior we observe. We show that access to insurance can partly offset this effect. Finally, we relate the observed experimental behavior to the propensity of respondents to take risks in their daily lives and show that an increase in risk-aversion has important implications for economic development.
Keywords: Q54; O12; D81; 330; natural disasters; risk aversion; development; Naturkatastrophe; Risikopräferenz; Risikoaversion; Entwicklung; Indonesien